Evolutionary history of HIV-1 Subtype B and CRF01_AE transmission clusters among men who have sex with men(MSM) in Kuala Lumpur, Malaysia - Ng, K.T.; Ong, L.Y.; Lim, S.H.; Takebe, Y.; Kamarulzaman, A.; Tee, K.K. (Public Library of Science, 2013)
HIV-1 epidemics among men who have sex with men (MSM) continue to expand in developed and developing countries. Although HIV infection in MSM is amongst the highest of the key affected populations in many countries in Southeast Asia, comprehensive molecular epidemiological study of HIV-1 among MSM remains inadequate in the region including in Malaysia. Here, we reported the phylodynamic profiles of HIV-1 genotypes circulating among MSM population in Kuala Lumpur, Malaysia. A total of n = 459 newly-diagnosed treatment-naı¨ve consenting subjects were recruited between March 2006 and August 2012, of whom 87 (18.9%) were self-reported MSM. Transmitted drug resistance mutations were absent in these isolates. Cumulatively, phylogenetic reconstructions of the pro-rt gene (HXB2:2253–3275) showed that HIV-1 subtype B and CRF01_AE were predominant and contributed to approximately 80% of the total HIV-1 infection among MSM. In addition to numerous unique transmission lineages within these genotypes, twelve monophyletic transmission clusters of different sizes (2–7 MSM sequences, supported by posterior probability value of 1) were identified in Malaysia. Bayesian coalescent analysis estimated that the divergence times for these clusters were mainly dated between 1995 and 2005 with four major transmission clusters radiating at least 12 years ago suggesting that active spread of multiple sub-epidemic clusters occurred during this period. The changes in effective population size of subtype B showed an exponential growth within 5 years between 1988 and 1993, while CRF01_AE lineage exhibited similar expansion between 1993 and 2003. Our study provides the first insight of the phylodynamic profile of HIV-1 subtype B and CRF01_AE circulating among MSM population in Kuala Lumpur, Malaysia, unravelling the importance of understanding transmission behaviours as well as evolutionary history of HIV-1 in assessing the risk of outbreak or epidemic expansion.